2017
DOI: 10.1080/03009734.2017.1408723
|View full text |Cite
|
Sign up to set email alerts
|

Do pregnant women want to know the sex of the expected child at routine ultrasound and are they interested in sex selection?

Abstract: BackgroundThe aim of the study was to investigate if expecting parents wanted to know the sex of the fetus during ultrasound examination and if they had discussed it with the midwife. Another aim was to explore any interest in sex selection.MethodsA longitudinal survey in early and late pregnancy among 2393 women in Sweden.ResultsAlmost all (95.8%, n = 2289) women had discussed sex determination with the partner before the ultrasound scan, and 57% (n = 1356) of women and their partners wanted to find out the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The sex selection of the offspring in mammalian species, including humans and other animals, often attracts critical attentions as well as interests in the society. Sex determination and sex selection in humans should be accompanied necessarily by the ethical consideration. Previous reports suggest that the preferred sex of the child may tend to reflect the parental background, including culture, tradition, religion, and education …”
Section: Introductionmentioning
confidence: 99%
“…The sex selection of the offspring in mammalian species, including humans and other animals, often attracts critical attentions as well as interests in the society. Sex determination and sex selection in humans should be accompanied necessarily by the ethical consideration. Previous reports suggest that the preferred sex of the child may tend to reflect the parental background, including culture, tradition, religion, and education …”
Section: Introductionmentioning
confidence: 99%
“…The previous studies reported that an increasing level of education leads to a decrease in believing in the 'evil eye' and food cravings; and at the same time leads to an increase in the belief that dietary may have an impact on the mental and physical development of the baby. 13,25,26,33 In the study, a statistically significant difference was found between the pre-test the average scores in terms of the desired gender of the baby variable (p<0.05) before the identification of the gender (1 st trimester), and the source of the difference was caused by the fact that the participants who preferred to have a boy also had a higher mean pre-test score. As mentioned in the study of Erbil and Saglam, the study conducted by Gol found that such kinds of practices are exercised more frequently by women who desired to have a boy.…”
Section: Resultsmentioning
confidence: 75%
“…As mentioned in the study of Erbil and Saglam, the study conducted by Gol found that such kinds of practices are exercised more frequently by women who desired to have a boy. 9,32,33 The limitation of this study is that it was conducted in a single center in Southeast Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13] With high consumer expectations and increased access to information, parents want to learn the sex of their fetus earlier in pregnancy. 5,10,14,15 With a small blood sample, parents can learn gender sooner, more reliably, and less expensively than ultrasound anatomy scans or other non-invasive prenatal tests. 6,12,[16][17][18][19] Compared to other methods available to parents, SneakPeek ® is the most accessible, affordable, and accurate choice for fetal sex determination.…”
Section: Introductionmentioning
confidence: 99%